Porcine circovirus type 3: immunohistochemical detection in lesions of naturally affected piglets - Molossi, Franciéli Adriane; Albuquerque de Almeida, Bruno; Santana de Cecco, Bianca; Pissetti, Caroline; Ventura, Lauren; Brandalise, Luciano; Simão, Gustavo; Vanucci, Fabio; Negrao Watababe, Tatiane Terumi; Vaz Jr., Itabajara da Silva; Driemeier, David (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the relationship between porcine circovirus type 3 (PCV3) viral load and histopathological findings in perinatal piglet tissues and to develop an immunohistochemical method for detecting the virus in lesions. The quantitative polymerase chain reaction (qPCR) cycle threshold (Ct) when amplifying PCV3 DNA and the area of perivascular inflammatory infiltrates in different organs (central nervous system [CNS], lung, heart, liver, spleen, and lymph nodes) were compared. To develop an immunohistochemistry technique, rabbit sera were produced against PCV3-capsid protein peptides selected using bioinformatic analyses. The assay was initially implemented using a tissue sample previously tested using qPCR and in situ hybridization to optimize the procedure and reagent dilutions. To evaluate immunohistochemistry performance, tissue samples from another 17 cases were analyzed using standardized parameters. The most common microscopic lesion was multisystemic periarteritis, with associated vasculitis, as the mesenteric vascular plexus is one of the most affected organs. Other tissues, such as the heart, lung, CNS, and skeletal muscle, were also affected. Comparison of the Ct values for different tissues showed no significant difference, except in lymphoid organs (spleen and lymph nodes), which had significantly higher viral loads than the CNS tissues. There was no correlation between Ct values and perivascular inflammatory infiltrates. PCV3 immunohistochemistry revealed granular immunolabeling, mainly in the cytoplasm of cells in the vascular mesenteric plexus, heart, lung, kidney, and spleen.